Development and evaluation of a fluid drill prototype - Rocha, Francisco Eduardo de Castro; Cruz, José Márcio da; Martyn, Peter John; Casali, Vicente Wagner Dias (Pesquisa Agropecuaria Brasileira, 2014)
A drill prototype, for sowing small seeds (1 to 5 mm in diameter) using a non-Newtonian fluid as a seed carrying medium and also as an initial source of moisture has been developed. In evaluating the performance of the machine, seeds of lettuce, onion and mustard were mixed with the fluid at different concentrations. The equipment has allowed different seed distributions, achieving crop sowing requirements.